Phantom - Nesbo Jo, 1960-; Bartlett, Don. (New York : Alfred A. Knopf, 2012)
Determined to prove the innocence of a young man he helped raise, disgraced former cop Harry Hole embarks on an increasingly dangerous investigation linked to Oslo's most virulent street drug.
"This is a Borzoi book"--T.p. verso
Keywords: Hole, Harry (Fictitious character) -- Fiction; Police -- Norway -- Oslo -- Fiction; Oslo (Norway) -- Fiction; Mystery fiction